Characteristics of Misinformation Spreading on Social Media During the COVID-19 Outbreak in China: A Descriptive Analysis - Chen K; Luo Y; Hu A; Zhao J; Zhang L (Dove Medical Press, 2021)
Kelin Chen,1 Yuni Luo,1 Anyang Hu,2 Ji Zhao,3 Liwei Zhang4 1Institute of Urban Governance, Shenzhen University, Shenzhen, 518060, People’s Republic of China; 2School of Government, University of Chinese Academy of Social Science, Beijing, 102488, People’s Republic of China; 3School of International and Public Affairs, Shanghai Jiao Tong University, Shanghai, 200030, People’s Republic of China; 4School of Public Administration, Jilin University, Changchun, 130012, People’s Republic of ChinaCorrespondence: Liwei ZhangSchool of Public Administration, Jilin University, 2699 Qianjin Street, Changchun, 130012, People’s Republic of ChinaEmail zhanglw@jlu.edu.cnBackground: During a public health emergency, social media is a major conduit or vector for spreading health misinformation. Understanding the characteristics of health misinformation can be a premise for rebuking and purposefully correcting such misinformation on social media.Methods: Using samples of China’s misinformation on social media related to the COVID-19 outbreak (N=547), the objective of this article was to illustrate the characteristics of said misinformation on social media in China by descriptive analysis, including the typology, the most-mentioned information, and a developmental timeline.Results: The results reveal that misinformation related to preventive and therapeutic methods is the most-mentioned type. Other types of misinformation associated with people’s daily lives are also widespread. Moreover, cultural and social beliefs have an impact on the perception and propaganda of misinformation, and changes in the crisis situation are relevant to the type variance of misinformation.Conclusion: Following research results, strategies of health communication for managing misinformation on social media are given, such as credible sources and expert sources. Also, traditional beliefs or perceptions play the vital role in health communication. To sum up, combating misinformation on social media is likely not a single effort to correct misinformation or to prevent its spread. Instead, scholars, journalists, educators, and citizens must collaboratively identify and correct any misinformation.Keywords: health misinformation, social media, public health emergency, health communication, COVID-19, China